2016
DOI: 10.1007/s10802-015-0125-5
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Socialization in Anxious Youth: Parenting Buffers Emotional Reactivity to Peer Negative Events

Abstract: Anxious youth exhibit heightened emotional reactivity, particularly to social-evaluative threat, such as peer evaluation and feedback, compared to non-anxious youth. Moreover, normative developmental changes during the transition into adolescence may exacerbate emotional reactivity to peer negative events, particularly for anxious youth. Therefore, it is important to investigate factors that may buffer emotional reactivity within peer contexts among anxious youth. The current study examined the role of parenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 73 publications
(79 reference statements)
1
29
0
4
Order By: Relevance
“…School-age children were more likely to have bad behavior during the epidemic. Previous study have indicated that school-age children have a certain ability to judge crisis and can use electronic products proficiently, and are susceptible to the negative information of the media network (White, 2017;Oppenheimer et al, 2016). Non-only children are more prone to bad behavior during the epidemic.…”
Section: Children's Behaviors and Parents' Mental Health Status Amongmentioning
confidence: 99%
“…School-age children were more likely to have bad behavior during the epidemic. Previous study have indicated that school-age children have a certain ability to judge crisis and can use electronic products proficiently, and are susceptible to the negative information of the media network (White, 2017;Oppenheimer et al, 2016). Non-only children are more prone to bad behavior during the epidemic.…”
Section: Children's Behaviors and Parents' Mental Health Status Amongmentioning
confidence: 99%
“…This development starts early, with parents helping younger children regulate their emotions through support and scaffolding (Kopp, 1989;Morris et al, 2007). As development progresses, parents continue to support and shape adolescent emotion regulation and foster emotional competencies (Morris et al, 2007;Oppenheimer et al, 2016), thus allowing adolescents to become better at regulating their/emotions independently (Morris et al, 2007). Morris et al (2007) suggested that there are three primary ways that parents shape adolescents' emotion regulation abilities: (a) emotion modeling, (b) specific parenting practices, and (c) family emotional climate.…”
Section: Parent Socialization Of Emotionmentioning
confidence: 99%
“…Additionally, responsive, structured, and supportive parent socialization has been found to be related to better self-regulation and lower internalizing and externalizing problems in children and adolescents (e.g., Klimes-Dougan et al, 2007;Oppenheimer et al, 2016;Rubin, Burgess, Dwyer, & Hastings, 2003). In contrast, research suggests that emotion dysregulation is shaped by a lack of supportive responses to adolescents' positive and negative emotions (e.g., Granic, 2005;Yap et al, 2007;Yap et al, 2008).…”
Section: Parent Socialization Of Emotionmentioning
confidence: 99%
See 2 more Smart Citations